Tunable Floating Capacitance Multiplier Using Single Fully Balanced Voltage Differencing Buffered Amplifier - Tangsrirat, W.; Channumsin, O. (My University, 2019)
Abstract: An alternative circuit configuration for realizing an electronically adjustable floating capacitance multiplier is presented in this article. By consisting of only one fully balanced-voltage differencing buffered amplifier (FB-VDBA), one resistor and one capacitor, the presented multiplier circuit is canonical structure, and does not require any critical element matching constrain. The equivalent value of the simulated capacitance is adjustable by tuning the bias current of the FB-VDBA. The effect of the FB-VDBA non-idealities on the realized capacitance has been considered in detail. The proposed floating capacitance multiplier has been utilized, as an example application, in the design of a second-order RLC band-pass filter. To support the theory, some computer simulations with PSPICE software are also reported.
Keywords: band-pass filter; capacitance multiplier; electronically tunable circuit; floating impedance simulator; fully balanced-voltage differencing buffered amplifier (FB-VDBA)